SPECIES COMPOSITION, DISTRIBUTION, ABUNDANCE AND VECTORIAL CAPACITY OF AN. FUNESTUS IN AN AFROTROPICAL ENVIRONMENT OF KATSINA STATE, NIGERIA. - Umar, Aliyu; Nock, I. H. (FUDMA JOURNAL OF SCIENCES, 2023)
The Anopheles funestus group is one of the major malaria vectors in tropical Africa; however, there is scanty data about the dynamics of members of this group. Consequently, a study was undertaken from 2009 to 2013 to establish the species composition, distribution and abundance and vectorial capacity of An. funestus in parts of Katsina State, Nigeria. Mosquitoes collected were identified morphologically using mosquito morphological keys of Hopkins (1952) and Gillies and Coetzee (1987). Authentication of the members of the Anopheles funestus group was done according to Cohuet et al. (2003) using the cocktail PCR method based on the ITS2 region developed by Koekemoer et al. (2002). The cocktail PCR-assay samples were 518 (51.24%) An. funestus s.s., 67 (6.624%) An. brucei and 35 (3.46%) An. rivoluru. Zone A recorded the highest preponderance of larvae at Dandume, 178 (32.8%) and the least abundance was 40 (7.4%) in Zone C at Katsina. Similarly, adults were more preponderant in Zone A at Funtua 88 (22.8 %) and were least abundant in Zone C at Daura with 28 (7.1%). The highest isolations for P. falciparum and P. malaria were 120 and 193 respectively in An. funestus s.s. and the lowest were 11 and 24 of P. falciparum and P. malaria respectively isolated from An. rivulorum. Pools and Rice farms breeding sites were only active during wet months, however ponds and reservoirs were active during both wet and dry months. There is significant Pearson Correlations between species (0.05 level: 1- tailed) and within An, funestus larvae.